Cotinine and cytokine levels in the vitreous body and blood serum of smokers and non-smokers – A pilot study. (November 2021) - List, Wolfgang; Singer, Christoph; Schwab, Christoph; Riedl, Regina; Plhak, Elisabeth Maria; Weger, Martin; Haas, Anton; Wedrich, Andreas; Seidel, Gerald
Abstract: Tobacco smoking is a risk factor for many ocular diseases. Of the multiple tobacco smoke compounds nicotine and its main metabolite cotinine are likely agents in disease modulation. The interaction of these compounds with exposed tissue is complex and ranges from proinflammatory to potentially neuroprotective properties. We aimed to determine cotinine and cytokines in the vitreous in smokers and non-smokers in this prospective, cross-sectional study at the Department of Ophthalmology, Medical University Graz, Austria. We included 10 smokers and 10 non-smokers. Vitreous and serum samples were analyzed for cotinine and cytokines. The cytokine analysis was performed with multiplex assay and cotinine was quantified with enzyme-linked immunosorbent assay. Cotinine was detectable in smokers only with a mean of 154.0 ng/ml ± 107.3 ng/ml in the vitreous and of 194.1 ng/ml ± 121.3 ng/ml in the serum. The difference between intraocular and systemic levels was statistically significant. There were no statistically significant differences between the cytokine levels of smokers and non-smokers. However, intravitreal VEGF-A was by trend elevated in smokers and correlated positively with intravitreal cotinine (r = 0.59, p = 0.073). In conclusion cotinine is detectable in the vitreous of smokers and is lower than the serum. There is a trend towards elevation of VEGF-A in the vitreous of smokers. Highlights: Nicotine and its metabolites alter the milieu in organs in immunosuppressive and pro-inflammatory ways. The nicotine metabolite cotinine is detectable in the vitreous of smokers and correlates with the intensity of tobacco consumption. Vascular endothelial growth factor A is a promising target for identifying pathways in smoking associated ocular pathologies.